2012
DOI: 10.1038/ejcn.2012.5
|View full text |Cite
|
Sign up to set email alerts
|

Dietary calcium intake and risk of type 2 diabetes: possible confounding by magnesium

Abstract: This study examined the association of dietary calcium intake with incident type 2 diabetes by a meta-analysis and explored the potential confounding by magnesium. Potential studies were identified by searching the PubMed database in September 2011. Prospective cohort studies that reported relative risks (RR) with 95% confidence intervals (CI) of type 2 diabetes for dietary calcium intake were selected. Results were combined using either a fixed-or random-effects model. Six prospective cohort studies comprisin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 12 publications
0
16
1
2
Order By: Relevance
“…The results related to the intake of calcium-rich foods (e.g., milk, cheese, and yogurt) have demonstrated reduced mortality due to CVD (6,7,24) and reduced risks of MI (15,24) and stroke (21,23,24). These studies have also demonstrated neutral or beneficial profiles for factors such as atherosclerosis (26)(27)(28), blood pressure (29), plasma glucose (30,31) and body weight (32).…”
Section: Dietary Calcium Supplementation Versus Medicinal Calcium Supmentioning
confidence: 93%
See 3 more Smart Citations
“…The results related to the intake of calcium-rich foods (e.g., milk, cheese, and yogurt) have demonstrated reduced mortality due to CVD (6,7,24) and reduced risks of MI (15,24) and stroke (21,23,24). These studies have also demonstrated neutral or beneficial profiles for factors such as atherosclerosis (26)(27)(28), blood pressure (29), plasma glucose (30,31) and body weight (32).…”
Section: Dietary Calcium Supplementation Versus Medicinal Calcium Supmentioning
confidence: 93%
“…Studies have demonstrated beneficial or neutral effects of calcium dietary intake and medicinal supplementation on the development of diabetes (30,31,77,78). A meta-analysis involving 264,268 participants and 11,225 reported cases did not find a correlation between dietary calcium intake and diabetes (30).…”
Section: Calcium and Diabetes Mellitusmentioning
confidence: 99%
See 2 more Smart Citations
“…Two meta-analyses of prospective studies concluded that Mg intake is inversely associated with type 2 diabetes [49,50]. Mg intake has been also strongly and inversely associated with the metabolic syndrome [37,51], while hypomagnesaemia has been independently associated with the development of impaired glucose tolerance [52].…”
Section: Issn: 2377-3634mentioning
confidence: 99%